Verzameling Sir Edward en Lady Hulton Londen. - Huggler, Max (Rotterdam : Museum Boymans van Beuningen, 1964)
Arp, Hans ; Cezanne, Paul ; Chagall, Marc ; De Chirico, Giorgio ; Degas, Edgar ; Dubuffet, Jean ; Fazzini, Pericle ; Gris, Juan ; Von Jawlensky, Alexei ; Kandinsky, Wassily ; Leger, Fernand ; Manzu, Giacomo ; Marini, Marino ; Matisse, Henri ; Modigliani, Amedeo ; Mondriaan ; Monet, Claude ; etc.
Verzameling Sir Edward en Lady Hulton Londen, Museum Boymans van Beuningen, Rotterdam, 27 november '64 - 17 januari '65
boek